Implementation of Digital Libraries as High School Welcome to the Era of Society 5.0 - Josep Kristian Lubis; Deswidya S Hutauruk (INFOKUM, 2022)
The school library is the only form of literacy implementation for students. With the development of information technology as it is today. Students cannot access knowledge outside their school by using existing digital libraries. The existence of the covid-19 pandemic has made not only students obstacle to getting direct knowledge from teachers but also teachers as teachers cannot carry out the learning process as usual, especially in a school that not even applying information technology in the field of education in their schools. SMA Negeri 1 Pangururan is one of the high schools in the capital city of Samosir Regency. With easy access in the Regency city, the school should have a capable digital library. Maintaining data for an extended period is one of the advantages obtained when implementing a digital library. The results of the study in the form of the application of a digital library with OPAC (Open Public Access Catalog using the Agile Development system development method) went well and smoothly, it was seen from the test results using black box testing, and the assessment of the application was in the "very feasible" status with a value of 81% so that the digital library is to be implemented in SMA Negeri 1 Pangururan.